Assessing Households’ Difficulties in Water Fetching and Latrine Use: A Case Study of Karnali Province, Nepal - Mahat, Laxmi Chandra (International Research Journal of MMC, 2026)
Over the past three decades Nepal has substantially extended its water and sanitation infrastructure and, in 2019, declared itself free of open defecation. Yet how access varies from one community to the next remains poorly understood, especially in lower-income provinces like Karnali. This study documents, at the household level, who struggles to fetch water and use a latrine, and how those struggles differ across social groups. Using a cross-sectional design, the author surveyed 800 households in Karnali, split evenly between Bhagabatimai Rural Municipality, Dailekh, and Birendranagar Municipality, Surkhet. Data were collected in 2024 using structured questionnaires administered on tablets using mWater platform. Chi-square tests related two yes-or-no difficulty measures to four characteristics: place of residence, self-assessed poverty, caste and ethnicity, and sex of the household head. In total, 8.1 percent of households reported difficulty fetching water and 8.5 percent difficulty with latrine use. The rural water-difficulty rate ran about seven times the urban rate, and the rural latrine rate roughly doubled the urban one. Dalit households were worst affected for water, while Dalit and Other households shared the highest latrine difficulty. Among those reporting trouble, physical impairment was the leading obstacle, ahead of vision and hearing problems. Together, the results expose rooted inequities tied to terrain, income, caste, and disability, pointing toward rural-focused, caste-aware, and disability-friendly investment to advance Sustainable Development Goal 6. Importantly, the study offers some of the first household-level, disaggregated evidence of WASH difficulty in Karnali, helping planners reach households that coverage data tend to hide.